1985
DOI: 10.1002/ijc.1985.36.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Amino Acid Sequence of Rabbit Tumor Necrosis Factor

Abstract: Good production of tumor necrosis factor (TNF) in the rabbit was obtained using Propionibacterium acnes IID 912 as a priming agent and subsequent administration of lipopolysaccharide. The physicochemical characteristics of rabbit TNF were very similar to those of murine TNF. The molecular weight of rabbit TNF was 39,000 as estimated by gel filtration, and 18,000 by SDS-PAGE. The isoelectric point was determined as pH 4.0 by isoelectric focusing. Rabbit TNF was stable within the pH range of 5.5 to 11.0, and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…TNF shows in vitro cytotoxic activity to a wide variety of human and animal malignant cell including cell lines and fresh cells of cancer patients in primary culture (Carswell et al 1975 ;Ha et al 1985 ;Haranaka et al 1985 ;Watanabe et al 1985). However, rTNF at the concentrations of 1 to 1,000 units/ml did not show any direct cytotoxicity to Meth A and Sarcoma-180 in primary culture (our unpublished results), indicating that the necrotic effect and the tumor regression are not direct action by rTNF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF shows in vitro cytotoxic activity to a wide variety of human and animal malignant cell including cell lines and fresh cells of cancer patients in primary culture (Carswell et al 1975 ;Ha et al 1985 ;Haranaka et al 1985 ;Watanabe et al 1985). However, rTNF at the concentrations of 1 to 1,000 units/ml did not show any direct cytotoxicity to Meth A and Sarcoma-180 in primary culture (our unpublished results), indicating that the necrotic effect and the tumor regression are not direct action by rTNF.…”
Section: Discussionmentioning
confidence: 99%
“…However, rTNF at the concentrations of 1 to 1,000 units/ml did not show any direct cytotoxicity to Meth A and Sarcoma-180 in primary culture (our unpublished results), indicating that the necrotic effect and the tumor regression are not direct action by rTNF. Several groups reported that TNF shows no toxicity to cultured Meth A (Carswell et al 1975 ;Ruff and Gifford 1981;Sugarman et al 1985;Yoshie et al 1986) except 3 groups (Ha et al 1985;Haranaka et al 1985 ;Kull et al 1985), although Meth A has TNF receptors (Kull et al 1985;Yoshie et al 1986). There is no correlation between the number of TNF receptors on the cell surface and expression of the cytotoxicity (Kull et al 1985;Yoshie et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralizing anti-rabbit IL-8 IgG and anti-rabbit GRO␣ IgG were raised in a goat, and purified with affinity column coupled with each chemokine (Matsukawa et al, 1997. Neutralizing anti-rabbit TNF␣ mAb was kindly provided by Dr. H. Nariuchi (The University of Tokyo, Japan) (Haranaka et al, 1985). Neutralizing anti-rabbit GRO␣ mAb (IgG1) was developed as described previously .…”
Section: Cytokines and Their Antibodiesmentioning
confidence: 99%
“…Endotoxin content was less than 0.9 ng/mg protein. Neutralizing anti-TNF-␣ mouse monoclonal antibody (IgG1) was purified on a HiTrap Protein G column (Pharmacia LKB Biotechnology, Uppsala, Sweden) from ascites of BALB/c mice bearing hybridoma 2-11E (a generous gift from Dr. H. Nariuchi, The University of Tokyo, Japan) [14]. Endotoxin content was less than 3.2 ng/mg protein.…”
Section: Reagentsmentioning
confidence: 99%